2018
DOI: 10.1128/jvi.01927-17
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-Electron Microscopy Structure of Seneca Valley Virus Procapsid

Abstract: Seneca Valley Virus, like some other members of the picornaviridae, forms naturally occurring empty capsids, known as procapsids. The procapsid has the same antigenicity as the full virion, so they present an interesting possibility for the formation of stable virus-like particles. Interestingly, although SVV is a livestock pathogen, it has also been found to preferentially infect tumour cells, and is being explored for use as a therapeutic agent in the treatment of small cell lung cancers. Here we used cryo-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Structures of mature SVV and the procapsid have been determined previously by crystallography and cryo-EM (19,20), and the binding of ANTXR1 to SVV has been visualized at low resolution (5,19). Structural comparison of the capsids suggests that SVV lies between aphthoviruses and cardioviruses, and is quite distant from enteroviruses (21).…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 97%
“…Structures of mature SVV and the procapsid have been determined previously by crystallography and cryo-EM (19,20), and the binding of ANTXR1 to SVV has been visualized at low resolution (5,19). Structural comparison of the capsids suggests that SVV lies between aphthoviruses and cardioviruses, and is quite distant from enteroviruses (21).…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 97%
“…The exogenous expression of TEM8 in non-permissive H69 and H146 SCLC cells allowed for effective SVV entry and killing. TEM8, but not CMG2 was also shown to directly bind SVV via co-immunoprecipitation studies ( 6 ) and cryo-electron microscopy of SVV-TEM8 mixtures revealed a regular labeling of SVV's capsid with TEM8 molecules, confirming its status as the SVV receptor ( 53 ).…”
Section: Tem8 Binds To Svv and Is Essential For Infectionmentioning
confidence: 95%
“…239 Furthermore, we showed that SVV binding site on ANTXR1 is non-conserved in its paralogous receptor, ANTXR2, which is expressed in normal cells, thereby providing a structural basis for tumor specificity of SVV. 240 SVV empty capsid binds ANTXR1, suggesting it may have potential as a vaccine or as virus-like particles for the development of tumor-targeted delivery of drugs. 240 As suggested from both functional and structural studies, the tumor tropism of SVV-001 is attributed to receptor-mediated internalization of the virus, a phenomenon common to other oncolytic picornaviruses.…”
Section: Seneca Valley Virusmentioning
confidence: 99%
“…240 SVV empty capsid binds ANTXR1, suggesting it may have potential as a vaccine or as virus-like particles for the development of tumor-targeted delivery of drugs. 240 As suggested from both functional and structural studies, the tumor tropism of SVV-001 is attributed to receptor-mediated internalization of the virus, a phenomenon common to other oncolytic picornaviruses. However, a successful SVV-001 infection may also require an additional innate immune defect.…”
Section: Seneca Valley Virusmentioning
confidence: 99%